Juridical Analysis Of Politics And International Law (Case Study Of Donald Trump's Attempted Assassination In The Context Of The History Of United States Political Violence) - Tinlaphas Chupantanarakul; Elza Zulia Futri; Ria Seftika; Riansyah Riansyah; Rima Elmisa (Universitas Malayati, 2025)
The purpose of this study is to find out how the growth of political violence in the US has significant implications in the context of international law. Other countries are paying attention to this situation because of its potential impact on regional stability and the world's democratic system. The research method used is normative juridical and data collection is carried out by literature study. The results of this study show: (1) The triggering factors for the increase in political violence in the United States are controversial political rhetoric, social and economic discontent, politicization of violence, and political instability in the United States. (2) the international political and legal perspective of the attempted assassination case of Donald Trump inthe context of international law, the country where the incident occurred has the responsibility to investigate and prosecute the perpetrators of the crime. In Trump's case, the reaction from Russia suggests that this situation could affect diplomatic relations between countries. This reflects how acts of violence against political leaders can have a wider impact in the international arena. Based on the results of the study, the author can conclude that international law plays an important role in responding to the attempted assassination of the former president, and the state's efforts to overcome political violence in the US involve a combination of law enforcement, public education, dialogue, preventive policies, and human rights protection. Furthermore, based on this conclusion, the author can give a suggestion that one of the main steps that must be taken in overcoming political violence is the strict enforcement of the federal and local laws. The federal and local governments, through agencies such as the FBI and local police, are tasked with investigating and cracking down on violations of the law related to political violence.